College Union Construction, 1968-01-21 - Missouri Southern State University (Missouri Southern State University (Joplin, Mo.), 1968)
#8 Missouri Southern College, College Union Looking Southwest ; Architect: Linscott-McArthur & Associates ; Contractor: M-P Construction Co. ; January 21, 1968